Strategi dan Tantangan: Kiprah TNI dalam Misi Perdamaian PBB - Arief Lassa Putra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2025)
The role of the Indonesian National Army (TNI) in global missions, especially peacekeeping under the auspices of the United Nations (UN), has become an important highlight in the context of international diplomacy and security, where since joining the UN peace mission, the TNI is committed to creating stability in conflict areas through the deployment of troops in various crisis countries. The founding fathers of our country included the obligation of the Republic of Indonesia to participate in maintaining world order in the 1945 Constitution, and the TNI is not only tasked with maintaining security, but is also active in community development, including providing humanitarian assistance and supporting the reconciliation process. With extensive training and experience, the TNI brings a human values-based approach, prioritizing cooperation with other countries and international organizations; The presence of the TNI in UN peacekeeping missions reflects Indonesia's commitment to global stability and strengthens the country's image in the international arena. In addition, this involvement serves as a means to increase TNI professionalism and expand the defense diplomacy network, where through various challenges faced in the field, the TNI's role not only has an impact on the recovery of conflict areas, but also creates positive synergies for world peace and security, showing that Indonesia is a country that cares and is responsible for maintaining global stability.